2020
DOI: 10.1017/s003118202000058x
|View full text |Cite
|
Sign up to set email alerts
|

Filarial worms: a systematic review and meta-analysis of diversity in animals from Iran with emphasis on human cases

Abstract: Current systematic review and meta-analysis demonstrate the prevalence reports of filariasis in animals in Iran along with human cases. Studies were screened, relevant papers were selected and the random-effect model was used by forest plot with 95% confidence interval (CI). Of 17 records of human case-reports, particularly from Khuzestan province (5 cases), Dirofilaria repens was the most detected parasite (10 cases) with higher involvement of the right eye (7 cases) than other organs. Eleven animal species w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 86 publications
0
6
0
Order By: Relevance
“…3 Distribution of D. immitis , D. repens and A. reconditum in dogs and humans of Iran. See Table 3 for data about dogs and references [ 8 , 9 , 70 ] for data about human cases …”
Section: Discussionmentioning
confidence: 99%
“…3 Distribution of D. immitis , D. repens and A. reconditum in dogs and humans of Iran. See Table 3 for data about dogs and references [ 8 , 9 , 70 ] for data about human cases …”
Section: Discussionmentioning
confidence: 99%
“…Dirofilaria spp. was reported in humans in Iran (Ashrafi et al 2010;Ghasemi et al 2020;Jamshidi et al 2008;Tavakolizadeh and Mobedi 2009), Israeli (Gutierrez et al 1995), and Taiwan (Li et al 2013), although these cases are not considered NTDs. Because the aim of the study was to document the situation of LF only in humans, the many studies that reported animal filariasis in Asia were excluded from the present analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The prevalence of D. immitis infection in dogs worldwide was 10.91% (95% CI = 10.18-11.65) in 2020. The prevalence of D. immitis in dogs varies across countries and continents, e.g., 22.68% in Australia, 12.07% in Asia, 11.60% in the Americas, 10.45% in Europe, and 7.57% in Africa [1]. Over the past few decades, the regional prevalence of D. immitis infection in dogs in Thailand has been reported as 10-58% in Bangkok [16,[29][30][31], 23-25% in the southern region [32], and 6-25% in the northern region [19,[33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…According to the World Health Organization (WHO) roadmap (WHO 2020), the goal of eliminating filariasis is expected to be achieved by 2030. Filarial infections are currently common in companion animals worldwide [1]. Specifically, in Southeast Asia, lymphatic filariasis caused by Brugia malayi (Brugian or Malayan filariasis), Wuchereria bancrofti (bancroftian filariasis) and Brugia timori is considered a significant human health problem.…”
Section: Introductionmentioning
confidence: 99%